PENINGKATAN HASIL BELAJAR SISWA MENGUNAKAN MEDIA MANIPULATIF PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Kristina, Kristina; Tampubolon, Budiman; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this thesis is to increase the learning outcomes of grade III student in learning mathematics in elementary school. The purpose of this thesis is to improve student learning outcomes in mathematics learning using manipulative media. The method used is descriptive. This form of research is a classroom action research consisting of 4 stages of processing, namely the planning stage, the implementation phase, the observation phase, and the reflection phase. Data collection tools used are observation sheets to measure the ability of teachers to plan and implement learning and test to measure student learning outcomes. The results of research that has been done obtained student learning outcomes in mathematics learning using manipulative media in grade III public Elementary Schools 15 Benteng Kecamatan Teriak Bengkayang has increased, in cycle 1 meeting 1 student who achieved completeness as many as 18 people (75,00%) with average grades average 70,83, in cycle 2 meeting 1 student who achieved completeness as many as 20 people (83,33%) with an average value of 76,88, and in cucle 3 meeting 1 student who achieved completeness as many as 22 people (91,67%) with average grades average 84,58. While in cycle 1 meeting 1 student who achieved completeness as many as 18 people (75,00%) with average grades average 69,58, in cycle 2 meeting 2 student who achieved completeness as many as 19 people (79,17%) with an average value of 74,79, and in cucle 3 meeting 2 student who achieved completeness as many as 22 people (91,67%) with average grades average 82,08. The conclusion is there is an increase in student learning outcomes in mathematics learning using manipulative media.Â Keywords: Improvement, Learning Outcomes, Manipulative Media, Mathematics